62nd Open Seminar on Acoustics and 91st Seminar of Czech Acoustical Society - Chronicle OSA 2015 (Archives of Acoustics)
The paper presents the abstracts presented during 62nd Open Seminar on Acoustics and 91st Seminar of Czech Acoustical Society.